Profiling of operating elements of gerotor screw compressor - V. A. Pronin; P. A. Belov; V. A. Tsvetkov; M. H. Dzhumaev; P. A. Egorov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение", 2025)
The gerotor screw compressor with internally meshing rotors is an innovative type of machines of the volumetric principle of compression of various gas media, which has a significant potential for expanding the applications of screw compressor technology. The main component of this compressor model is an internally meshed screw pair, the methodology of profiling of which has remained insufficiently studied. The paper presents a computational model for the operating element profiling based on the theory of cycloidal meshing, including the generation of front profile coordinates and helical formations for rotors with different profile types. The article develops an algorithm for generating geometric 3D models using solid modeling software.